Pseudoceros astrorum, a new species of Polycladida (Cotylea, Pseudocerotidae) from Northeastern Brazil - Bulnes, Verónica Natalia (2014)
Pseudoceros astrorum n. sp. is characterized by a smooth dorsal surface with a brown ground colour, and with net-like pattern of small black granules, white spots of different sizes uniformly distributed, a thin black sub-marginal band, and a white marginal rim. The pseudotentacles are dark brown with white tips and the anterior margin and cerebral region is devoid of pigmentation. The male system is characterised by conspicuous spermiducal bulbs, a conical curved penis stylet, and the sucker lies more or less posterior. With this contribution, the number of known species from Brazil is now 72, and has created new interest in the lesser-known polyclad fauna from the northeast coast of Brazil.